Extension, school and environment: A training experience for students of the university teacher training program in agricultural sciences at the National University of Misiones (Itinerarios Educativos, 2025)
This paper presents a university extension experience carried out in 2025 between the university teacher training program of Agricultural Sciences of the Faculty of Forest Sciences, National University of Misiones (UNaM), and San Vicente de Paul Family Farming School (EFA) both institutions with territorial influence in the town of San Vicente, Misiones Province, Argentina. The proposal, which was developed by the departments of Professional Teaching Practice II, Professional Teaching Practice III and Pedagogical Residency departments, aimed to promote the early exposure of future teachers to the institutional and pedagogical reality of a secondary agricultural school. Through activities designed using project–based teaching methodology and supported by playful and didactic strategies, the program promotes the development of fundamental competencies for teaching, such as planning, collaborative work, group coordination, and critical reflection on teaching practice. The experience was structured around Environmental Education themes, addressing issues specific to the regional context and agricultural activity. This initiative, which has been underway since 2019, strengthens ties between the university and partner schools, recognizing them as co–educational spaces and rewarding their commitment to the practical training of student teachers.
Keywords: University teacher training; project–based learning; Environmental Education; agricultural sciences